Possibilities of Self-Control When Drawing and Copying in Older Preschool Children With Mental Retardation (Message 1) - Kovalenko O. M. (Current trends in the development of education system, 2022)
The article is devoted to the study of the possibilities of correcting mistakes made when drawing and copying by children of older preschool age with mental retardation. The article presents options for correcting children of older preschool age with a mental retardation of their drawings in the course of organized self-control.
Keywords: задержка психического развития; самоконтроль; self-control; старший дошкольный возраст; ЗПР; антонимические связи и отношения; графические средства; mental retardation (MPD); older preschool age; antonymic connections and relationships; graphic tools